Serial Cerebral Metabolic Changes in Patients With Ischemic Stroke Treated With Autologous Bone Marrow Derived Mononuclear Cells - Haque, Muhammad E.; Gabr, Refaat E.; George, Sarah D.; Boren, Seth B.; Vahidy, Farhaan S.; Zhang, Xu; Arevalo, Octavio D.; Alderman, Susan; Narayana, Ponnada A.; Hasan, Khader M.; Friedman, Elliott R.; Sitton, Clark W.; et al. (Frontiers in Neurology, 2019)
Purpose: Cell-based therapy offers new opportunities for the development of novel treatments to promote tissue repair, functional restoration, and cerebral metabolic balance. N-acetylasperate (NAA), Choline (Cho), and Creatine (Cr) are three major metabolites seen on proton magnetic resonance spectroscopy (MRS) that play a vital role in balancing the biochemical processes and are suggested as markers of recovery. In this preliminary study, we serially monitored changes in these metabolites in ischemic stroke patients who were treated with autologous bone marrow-derived mononuclear cells (MNCs) using non-invasive MRS. Materials and Methods: A sub-group of nine patients (3 male, 6 female) participated in a serial MRS study, as part of a clinical trial on autologous bone marrow cell therapy in acute ischemic stroke. Seven to ten million mononuclear cells were isolated from the patient’s bone marrow and administered intravenously within 72 hours of onset of injury. MRS data were obtained at 1, 3, and 6 months using a whole-body 3.0T MRI. Single voxel point-resolved spectroscopy (PRESS) was obtained within the lesion and contralesional gray matter. Spectral analysis was done using TARQUIN software and absolute concentration of NAA, Cho, and Cr was determined. National Institute of Health Stroke Scale (NIHSS) was serially recoreded. Two-way analysis of variance was performed and p<0.05 considered statistically significant. Results: All metabolites showed statistically significant or clear trends toward lower ipsilesional concentrations compared to the contralesional side at all time points. Statistically significant reductions were found in ipsilesional NAA at 1M and 3M, Cho at 6M, and Cr at 1M and 6M (p<0.03), compared to the contralesional side. Temporally, ipsilesional NAA increased between 3M and 6M (p<0.01). On the other hand, ipsilesional Cho showed continued decline till 6M (p<0.01). Ipsilesional Cr was stable over time. Contralesional metabolites were relatively stable over time, with only Cr showing a reduction 3M (p<0.02). There was a significant (p<0.03) correlation between ipsilesional NAA and NIHSS at 3M follow-up. Conclusion: Serial changes in metabolites suggest that MRS can be applied to monitor therapeutic changes. Post-treatment increasing trends of NAA concentration and significant correlation with NIHSS support a potential therapeutic effect.